(untitled) (Scientific journal of the Fergana State University, 2026)
This article provides detailed information about the importance of general physical training, its role in ensuring an individual’s physical maturity, and its place in the process of physical development. General physical training creates a necessary foundation for health improvement and physical development by uniformly cultivating an individual’s physical qualities, including strength, speed, agility, endurance, and flexibility. The article discusses the tools of physical training, including exercises with and without equipment, as well as important exercises such as walking, running, and others that play a significant role in developing movement qualities. Additionally, it provides information on how general physical training serves as a basis for health enhancement and specialized physical training. The article includes weight norms based on height and chest width for both men and women, which can be used to assess the individual level of physical training. This article is an important resource for individuals engaged in physical education and sports.